Numerical Simulation Study on The Effect of Isolated Coal Pillar Width on The Subsidence Law of Deep Mining - Yao, Jianping (International Journal of Natural Resources and Environmental Studies, 2024)
A large number of research results show that the reasonable determination of the width of the coal pillar is an important factor affecting the stability of the surrounding rock along the roadway along the fully mechanized discharge. In this paper, the mechanism of the specific condition of isolation of coal pillars in the deep roadway of Menkeqing coal mine area on the law of surface subsidence is analyzed. The FLAC3D numerical simulation technology was used to simulate the multi-level experimental scheme to analyze the influence of different remaining coal pillar widths on the stress and strain of overburden rock and surface subsidence, and to reveal the relationship between the width of isolated coal pillars and the surface subsidence law of deep mining.